Další vzdělávání ve zdravotnictví - Zezulková, Jana (Univerzita Tomáše Bati ve Zlíně, 2006)
Cílem této bakalářské práce bylo zaměřit se na zmapování přístupu pracovníků ve zdravotnictví k dalšímu, celoživotnímu vzdělávání. Protože oblast dalšího vzdělávání je značně rozsáhlá, zaměřuje se tato práce pouze na některé její části. Práce obsahuje teoretické informace o výchově a vzdělávání jak v obecné, tak i v legislativní rovině. Dále je přiblížen pojem celoživotního vzdělávání ve zdravotnictví z hlediska organizací působících v tomto odvětví. Analýzou prostředí zvolené organizace se došlo k závěru, že doposud nabízené možnosti pokrývají většinu potřeb zaměstnanců organizace a že sami zaměstnanci mají pozitivní přístup k celoživotnímu vzdělávání. K nejvyužívanějším metodám vzdělávání se řadí seminární školení, odborné stáže a kurzy. The subject of this thesis is a Further Education of the Medical Staff. The main body of this essay focuses on the medical staffs attitude to a continuous lifetime education and professional training. The Further education in the medical field is a very complicated issue, therefore this thesis deals with its most important aspects. It contains the theoretical base as well as the legislative background of the solving problem. It is based on the analyze of the internal environment of a medical organisation. The point of view of the organisation is taken into consideration to fulfill the objectives and to find the optimal solution. The conclusion says that most of the staff needs and requests in the field of further education are well satisfied in the present system and that the staff has a very positive attitude to a further education and lifelong professional training. The most common methods of the further education and professional training in the medical field are the professional courses, seminar meetings and internships. Ústav pedagogických věd obhájeno